Development of a Patient Decision Aid for Adults in China with Type 2 Diabetes Considering Add-on Antihyperglycemic Agents for Good Glycemic Control After Failure with Metformin Monotherapy - Zheng, Hui (Université d'Ottawa / University of Ottawa, 2021)
Patients with type 2 diabetes mellitus (T2DM) in whom metformin monotherapy is insufficient to achieve good glycemic control face challenges to choose among treatment options when considering treatment intensification. The objective was to develop a patient decision aid (PDA) prototype for these patients with T2DM in China in supporting them to make an informed decision. First, a patient decisional needs assessment was conducted at Fu Wai Hospital, China to gain insight into the values and preferences of patients in China in making this treatment decision. Second, a systematic review and network meta-analysis was conducted of the comparative efficacy and safety of eight antihyperglycemic classes combined with metformin in treating patients with T2DM. Third, the results of the first two objectives were integrated into developing a prototype of a PDA for patients with T2DM considering the addition of an agent after metformin monotherapy failure in achieving sufficient glucose control.
Keywords: Bayesian network meta-analysis; Systematic review; Type 2 diabetes mellitus; Antihyperglycemic drug classes; Patient needs assessment in China; Patient decision aid